Cummins in China - Rosenthal, Jean W., 1945- (London : Yale School of Management, 2016)
Cummins had combined its global expertise with solutions developed in China for the China market. But the introduction of each new level of emissions standards came with regulatory uncertainty. To meet the needs of the China market, engines had to be less expensive and more fuel efficient than engines developed to meet similar standards in North America and the U.S. Even more challenging, the uncertainty around implementation of each new round of emissions standards made it difficult for Cummins to plan its manufacturing and meet its Mission Statement.
Originally published in Rosenthal, J. (2016). Cummins in China. 16-011. New Haven, CT: Yale School of Management, Yale University. Retrieved from: https://vol11.cases.som.yale.edu/cummins-china.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Cummins, Inc; Internal combustion engine industry -- Environmental aspects -- China; Air quality -- Standards -- China; Mission statements -- China